2022
DOI: 10.1136/bmj-2022-072826
|View full text |Cite
|
Sign up to set email alerts
|

Can artificial intelligence pass the Fellowship of the Royal College of Radiologists examination? Multi-reader diagnostic accuracy study

Abstract: Objective To determine whether an artificial intelligence candidate could pass the rapid (radiographic) reporting component of the Fellowship of the Royal College of Radiologists (FRCR) examination. Design Prospective multi-reader diagnostic accuracy study. Setting United Kingdom. Participants One artificial intelligence candidate (Smarturgences, Milvue) and 26 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…7 Overall, approaches using LLMs have shown that they can perform relatively well in a variety of medical testing situations. 4,5 These scores are sure to improve, perhaps rapidly, and tools like ChatGPT may become ubiquitous, much the way various forms of AI are currently used in clinical and research genomic analyses every day. 8,9 As one of many examples, patients and research subjects may increasingly turn to ChatGPT and other such interfaces to learn about conditions that may affect them, including the suggested work-up and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Overall, approaches using LLMs have shown that they can perform relatively well in a variety of medical testing situations. 4,5 These scores are sure to improve, perhaps rapidly, and tools like ChatGPT may become ubiquitous, much the way various forms of AI are currently used in clinical and research genomic analyses every day. 8,9 As one of many examples, patients and research subjects may increasingly turn to ChatGPT and other such interfaces to learn about conditions that may affect them, including the suggested work-up and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Recently, large-language models (LLMs) like ChatGPT (https://chat.openai.com/chat) have been receiving attention in many venues, including via demonstration of medical knowledge. 4,5 By way of background, LLMs use a specific type of DL called a transformer. By training the model on a large dataset of text, it learns to predict the next word in a sentence or set of words following a prompt such as a question.…”
Section: Introductionmentioning
confidence: 99%
“…This algorithm can detect seven different pathologies (fracture, pleural effusion, lung opacification, joint effusion, lung nodules, pneumothorax, and joint dislocation). A recent study which compared this AI algorithm’s ability to human radiologists showed that the algorithm failed to pass the Fellowship of Royal College of Radiologists Rapid Reporting examinations [ 57 ]. This exam is normally taken between radiology speciality training years four and five in the UK [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Now, Susan Shelmerdine and UK based co-authors have asked whether an artificial intelligence candidate could pass the Fellowship of the Royal College of Radiologists (FRCR) examination, which allows radiology candidates to obtain the diploma for the licence to practise (doi:10.1136/bmj-2022-072826). 9…”
mentioning
confidence: 99%